Training of force versus training of endurance. Exists compatibility? - Ide, Bernardo Neme (2012)
The concurrent training phenomenon was first described in 1980 by Robert C. Hickson. At the molecular level, there seems to be an explanation for the interference of strength development because different forms of exercise induce antagonistic intracellular signaling mechanisms of protein synthesis that, in turn, could have a negative impact on the muscle's adaptive response. Precisely, recent studies have shown antagonistic activities between the anabolic signaling mechanisms induced by PI3k/mTOR/PKB/S6kl/4E-BP, and the energy-modulating signaling by AMPK. Furthermore, the manipulation of acute strength and endurance training variables (e.g., volume, intensity, contraction velocity, muscle actions) results in distinct adaptations, different magnitudes of activation of mTORand AMPK signaling pathways, and thus muscle hypertrophy. The purpose of this review is to describe the phenomena of concurrent training, examine the potential mechanisms that may explain the inhibition of strength development and suggest new studies analyzing the results from distinct intensities and volumes of strength and endurance training.